Pendampingan Pelaporan Keuangan Melalui Platform Digital - Siti Aminah, Neng Hasnah; Salmawinata, Ilona; Safira, Mila; Nurrizqa, Rindiani Restu; Linuhung, Tiara Setra; Mediawati, Elis (Jurnal Ilmiah Pangabdhi, 2023)
The use of financial applications for most MSMEs is still quite low, even though having financial reports is a must in every business activity. The financial application will produce a financial report that can help business actors to analyze the development of their business and make the right business decisions. This mentoring program aims to encourage the improvement of the financial performance of Ngetan MSMEs as partners in managing finance based on the use of information technology through a financial application called Accountingku. The use of this financial application is expected to make it easier for partners to start familiarizing themselves with financial reports as the output of business financial records. The mentoring method used is through observation and interviews with partners to find out their business activities. In addition, assistance is also carried out by holding video conferences through the Google Meet application to demonstrate applications that support the recording of selected financial statements. The results of this mentoring program show that partners are quite proficient in operating the Akuntansiku application and understand financial statements in general.